What is the near-natural catchment? An application of hydrological signatures assessment - Huan Xu; Hao Wang; Pan Liu; Xiaojing Zhang; Weibo Liu; Chutian Zhou; Hao Ye; Hongxuan Lei; Yang Liu (Ecological Indicators)
Many studies classify catchments with little human activity (HA) as near-natural catchments to increase the number of studied catchments. However, how much HA can be negligible is still unclear. In this study, catchments with little HA are classified as near-natural catchments when their hydrological behavior is similar to that of natural catchments. To determine whether a catchment can be considered near-natural, we derive several key hydrological signatures that characterize catchment behavior among numerous hydrological signatures. This is done by condensing a large set of 222 into eight signatures that are computable, representative, robust, and predictable. The sensitivity of the eight signatures to HA are calculated using a causal inference method instead of directly calculating linear correlation coefficients to avoid spurious relationships. The product of sensitivity and HA represents the HA impact on the catchment. By limiting the impact to a small proportion of the average hydrological signature, the HA threshold is determined. Results in the global catchments show that HA thresholds are 0.8%, 1.2%, and 15.4% of the city area, cropland area, and reservoir regulation degree, respectively. Both hypothesis testing and visual inspection indicate that catchments with the determined thresholds exhibit hydrological behavior identical to that of natural catchments. Based on these thresholds, approximately 68% of the world’s land area, excluding Antarctica, is classified as near-natural catchments. This study established a method to identify the negligible degree of HA using causal relationships. It contributes to the understanding of the HA impact on hydrological systems.